2007
DOI: 10.1063/1.2823602
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between photoluminescence and magnetic properties of GaMnN films

Abstract: GaMnN films grown by metal-organic chemical vapor deposition were studied by photoluminescence ͑PL͒ spectroscopy and hysteresis measurements. Depending on the growth conditions of these GaMnN films, hysteresis measurements along the easy axis of magnetization show a transformation from magnetic to nonmagnetic behavior. The PL spectra of both magnetic and nonmagnetic GaMnN films exhibited GaN band edge and deep-level impurity transitions at 3.4 and 1.3 eV, respectively. The PL emission intensity of the 1.3 eV e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…These researchers schematically illustrated the mechanism responsible for the formation of ZPL. The value of ZPL agrees with the calculated energy difference of 1.4 eV between the antibonding t 2 states and the e states for the trivalent Mn by density-functional theory [34], and it differs from that of 1.3 eV reported in previous literature [35], where fine structures were not resolved in the PL spectra. In the present work, the correlation of ZPL and its replicas with Mn 3+ can account for both the decreased intensity (the R line of sapphire can serve as a reference) and the complete disappearance of the emission band from 850 nm to 980 nm in the spectra of films B and A in Fig.…”
Section: Resultssupporting
confidence: 73%
“…These researchers schematically illustrated the mechanism responsible for the formation of ZPL. The value of ZPL agrees with the calculated energy difference of 1.4 eV between the antibonding t 2 states and the e states for the trivalent Mn by density-functional theory [34], and it differs from that of 1.3 eV reported in previous literature [35], where fine structures were not resolved in the PL spectra. In the present work, the correlation of ZPL and its replicas with Mn 3+ can account for both the decreased intensity (the R line of sapphire can serve as a reference) and the complete disappearance of the emission band from 850 nm to 980 nm in the spectra of films B and A in Fig.…”
Section: Resultssupporting
confidence: 73%
“…Based on the results, the Mn-related IB band could be suggested, which were first evidenced by electrical pumping to probe the position of the Mn-related energy states, to form at lower than the middle of the GaN bandgap in the Mn-doped GaN. These findings based on the EL spectra were consistent with the previous experimental results based on PL and/or transmittance and theoretical expectation 9 , 23 , 38 . In addition, preliminary results showed that the two-photon absorption process via the IB operation could lead to a positive impact on the conversion efficiency of the GaN p-i-n solar cells with the Mn-doped absorption layer 21 .…”
Section: Resultssupporting
confidence: 87%
“…Research on diluted magnetic semiconductors (DMSs), especially GaMnN, has received much attention due to their potential for the integration of photonic, electronic, and magnetic devices on a single chip. [1] Some properties such as the nature of the electronic states and the light emission mechanism are essential for electro-optical properties and spintronic devices. In this aspect, the most relevant and significant issue is the natural state of the Mn doped into GaN.…”
Section: Introductionmentioning
confidence: 99%